THE ISSUE OF WOMEN AT THE SCIENTIFIC HERITAGE OF JADID THINKERS - Togayeva Dilnavoz Narzikulovna (Scholar Express Journal, 2022)
This article analyzes the views of the family, women and social etiquette in the scientific heritage of Abdurauf Fitrat, Avloni, Qori Rahmatullah Vozeh, who have a unique place in modern literature and philosophy. The article also provides a socio-philosophical analysis of the spiritual and enlightenment views of the family in the works of the Jadids from a contemporary perspective
Keywords: Globalization; Family; Wedding; Scholars; Freedom